EDUCATION AND DEVELOPMENT: A Comparative Cost-Benefit Analysis of Bihar and Kerala - Johnson, Irene; Panchamukhi, Pushkarni (IJRDO - Journal of Social Science and Humanities Research, 2022)
India’s multitudes of diversities are not limited to its culture, but also reflected in the varying positions of each state in human and economic development. Two states on the opposite extremes since the inception of India are Kerala and Bihar, causing variances in the average indices of the nation. Though there are differences in their GDP and per capita incomes, the stark contrast in their literacy rates, levels of educational attainment and gender roles have stood them apart. Based on the endogenous growth model, the contrasting relationships between education and development in these two states were analysed under the framework of cost-benefit analysis. The acclaimed ‘Kerala Model’ was demystified and critically analysed to test its applicability on improving the position of Bihar from the lowest rungs in the human development index. A real-time example of the importance of planned investment in human capital and its subsequent externalities to the society was examined through the different COVID-19 responses of the states.